Full Stack FastAPI, React, and MongoDB. - Marko Aleksendrić; Shrey Batra; Rachelle Palmer; Shubham Ranjan; PACKT (GB: Packt, 2024)
Boost your web developer potential and stay ahead in the fast-paced web development and AI race with the flexibility, adaptability, and robustness of the FARM stack Key Features Learn the basics of MongoDB to be able to model any type of data Explore the powerful Python web development ecosystem with Pydantic and FastAPI Future-proof your applications by integrating ChatGPT or other LLMs Purchase of the print or Kindle book includes a free PDF eBook Book Description Discover how to harness the power of the FARM stack-FastAPI, React, and MongoDB-to develop production-ready web applications of varying complexity. Written by a team of industry experts, including MongoDB champions and product leaders, this fast-paced, hands-on guide equips beginners with essential skills to build web applications efficiently. Introducing each element of the stack, the book demonstrates how to seamlessly integrate them to create a medium-sized web application. You'll set up MongoDB as a document store, construct a simple API with FastAPI, and build an application using React. The guide also covers enhancing application security through authentication and authorization with JSON Web Tokens. Beyond mastering the stack, you'll get to grips with integrating Large Language Models (like ChatGPT) for advanced functionality, such as automated email sending. Additionally, you'll learn how to make the most of Next.js 14, a robust full-stack framework offering improved developer experience. By the end of the book, you'll have created functional applications and gained the foundation to explore diverse and more specialized domains, expanding your development horizons. What you will learn Set up and manage MongoDB databases and collections, and model data Leverage the power of FastAPI to write complex APIs using pure Python Create frontends of varying complexity with the React library Build and deploy robust and secure backends using FastAPI and MongoDB Ship production-ready applications with Next.js 14, applying your React and backend knowledge Integrate Large Language Models, send emails, and do much more with the flexible FARM stack Who this book is for The book is for intermediate web developers with basic JavaScript and Python knowledge who want to enhance their developer skills, master a powerful and flexible stack, and write better applications faster.
Data in extended ASCII character set.
Mode of access: Internet.